2022
DOI: 10.1038/s41467-021-27908-y
|View full text |Cite|
|
Sign up to set email alerts
|

Following excited-state chemical shifts in molecular ultrafast x-ray photoelectron spectroscopy

Abstract: The conversion of photon energy into other energetic forms in molecules is accompanied by charge moving on ultrafast timescales. We directly observe the charge motion at a specific site in an electronically excited molecule using time-resolved x-ray photoelectron spectroscopy (TR-XPS). We extend the concept of static chemical shift from conventional XPS by the excited-state chemical shift (ESCS), which is connected to the charge in the framework of a potential model. This allows us to invert TR-XPS spectra to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 56 publications
3
31
0
Order By: Relevance
“…In the following sections, we compare experimental results with 3D simulations performed for a chirped electron beam. The energy chirp along the lasing fraction of the bunch was set to 150 keV/fs (Figure 2), leading to a spectral width of about 1% for the XUV pulse, in agreement with several spectral measurements performed at FLASH [5,[22][23][24]. The chirp in the electron bunch leads to a chirp of 30 meV/fs in the 13.5 nm XUV pulse, or, expressed as second-order dispersion, it yields a value of 25 fs 2 , which is comparable to the measurements described in Ref.…”
Section: Sase Fel Amplification Processsupporting
confidence: 80%
“…In the following sections, we compare experimental results with 3D simulations performed for a chirped electron beam. The energy chirp along the lasing fraction of the bunch was set to 150 keV/fs (Figure 2), leading to a spectral width of about 1% for the XUV pulse, in agreement with several spectral measurements performed at FLASH [5,[22][23][24]. The chirp in the electron bunch leads to a chirp of 30 meV/fs in the 13.5 nm XUV pulse, or, expressed as second-order dispersion, it yields a value of 25 fs 2 , which is comparable to the measurements described in Ref.…”
Section: Sase Fel Amplification Processsupporting
confidence: 80%
“…Experimental data confirmed that a soft X-ray FEL source is very effective in timeresolved PECD for studying dissociating chiral cations [34] and for time-resolved photoelectron spectroscopy (XPS) applied to site-specific analysis suitable to distinguish the contributions of different atoms of the same chemical element simultaneously probed [35]. Following these promising results, Faccialà et al investigated at the C K-edge the chirality of fenchone, a prototypical organic molecule, using both time-resolved XPS and PECD [36].…”
Section: -3 the Electronic Structure Of Photo-excited Chiral Moleculesmentioning
confidence: 69%
“… 10–12 A prerequisite for any control of electronic and nuclear dynamics toward specific molecular reaction pathways is a detailed analysis of structural properties, when the molecule is driven out of equilibrium and here, in particular, the analysis of the time-dependent electronic structure defining the potential energy landscape in which the nuclei move. 13 X-ray photoelectron spectroscopy (XPS) is a well-established technique sensitive to the electronic structure. Applied in a time-resolved pump-probe scheme, it allows us to unambiguously monitor electronic coherences and vibronic coupling long before fragmentation sets in, i.e., while the electronic wave packet propagates.…”
Section: Introductionmentioning
confidence: 99%